Tingkat Erosi Berbasis Data Spasial di Das Taipa Kota Palu - Palar, Eddy Sugandi; Akhbar, .; Arianingih, Ida (Jurnal Warta Rimba, 2018)
This the study was conducted in Taipa, Palu Utara Regency of Palu City. The aims of this study to identify the attrition rate based on slope and river flow pattern used SPOT 6 of 2014 in Taipa watersheds. Method of the study was classification technique of image SPOT-6 2014, which to classify the river flow patterns and the gradual slope to find out the level of erosion in Taipa watersheds, Palu Utara Regency of Palu City. The results of calculation through image SPOT 6 of 2014 along with data covering this study that a very large erosion rate occurs at level 3 is 1181,02 ha, which is based on the relationships between slope classes and river flow. Based on data analysis of Rate of Erosion Hazard (TBE) the greater value of erosion rate then greater also the erosion hazard, so that the appropriate action is needed to reduce the level of erosion hazard in order to minimize the extent of changes that might occur. The value of X2 = 60.398,37, T table = 32.000, then 60.398,37 > 32.000 = Ha is accepted. Based on T counted and T table, then it can be found there is a correlation between the rate of erosion and slope classes used image SPOT 6. It can be stated that T counted is greater than T table. This correlation is based on the assumption that the other variables are same, which different only the slope. If the other variables are not similar, for examples rockresistance or the different land cover, then the correlation would be different also.Keywords: Erosion Rate, Spasial Data, Watersheds Taipa